A4: Efficacy and Safety of Tocilizumab in Patients With Polyarticular‐Course Juvenile Idiopathic Arthritis: 2‐Year Data From CHERISH. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Brunner, Hermine; Ruperto, Nicolino; Zuber, Zbigniew; Cuttica, Rubén J.; Xavier, Ricardo; Calvo, Inmaculada; Rubio, Nadina; Alekseeva, Ekaterina; Chasnyk, Vyacheslav; Chavez, Jose; Horneff, Gerd; Opoka‐Winiarska, Violetta; et al.
Abstract : Background/Purpose: The efficacy and safety of tocilizumab (TCZ), an interleukin‐6 receptor inhibitor, were previously demonstrated at week 40 of CHERISH, a phase 3 trial in patients with polyarticular‐course juvenile idiopathic arthritis (pcJIA) (1 ). Here we report the efficacy and safety of TCZ over 104 weeks of treatment in patients with pcJIA. Methods: Patients 2 to 17 years old with ≥6 months' active pcJIA who failed methotrexate received open‐label TCZ (weight ≥30 kg, 8 mg/kg [n = 119]; weight ≥30 kg, randomly assigned [1:1] to 8 [n = 34] or 10 [n = 35] mg/kg) every 4 weeks for 16 weeks. Patients with ≥JIA American College of Rheumatology (ACR) 30 response at week 16 entered a 24‐week, double‐blind withdrawal period and were randomly assigned (1:1) to placebo or continuation with TCZ. Patients with JIA ACR30 flare or who completed the withdrawal period entered an open‐label extension through week 104. Results: One hundred eighty‐eight patients entered the lead‐in period, 166 entered the withdrawal period, 160 entered the open‐label extension period, and 155 completed 104 weeks. In patients who received continuous TCZ throughout the study (n = 82), JIA ACR responses, improvement in JIA ACR core components, and proportions of patients with inactive disease or remission (1 ) were maintained through week 104. JADAS‐71 scores were maintained through week 104 (Figure); 73% of patients had JADAS‐71 <3.8 (minimal disease activity cutoff), 56% had JADAS‐71 <1 (inactive disease cutoff). The safety population comprised 188 patients with 307 patient‐years (PY). Rates/100 PY of adverse events (AEs) and serious AEs (SAEs) were 406.5 and 11.1, respectively; infections were the most common AE (151.4) and SAE (5.2). ALT and AST elevations ≥3× upper limit of normal occurred in 6.4% and 2.7% of patients, respectively. Grade 3 lowest neutrophil count and grade 2/3/4 thrombocytopenia occurred in 5.9% and 1.6% of patients, respectively. LDL cholesterol ≥110 mg/dL occurred in 16.2% of patients. Conclusion: The efficacy of TCZ was maintained through 2 years of treatment in patients with pcJIA, with no change in safety profile from that reported previously (1 ).